Two-component regulatory systems in Helicobacter pylori and Campylobacter jejuni: Attractive targets for novel antibacterial drugs - Casado, Javier; Lanas, Ángel; González, Andrés (Frontiers in Cellular and Infection Microbiology, 2022)
Two-component regulatory systems (TCRS) are ubiquitous signal transduction mechanisms evolved by bacteria for sensing and adapting to the constant changes that occur in their environment. Typically consisting of two types of proteins, a membrane sensor kinase and an effector cytosolic response regulator, the TCRS modulate via transcriptional regulation a plethora of key physiological processes, thereby becoming essential for bacterial viability and/or pathogenicity and making them attractive targets for novel antibacterial drugs. Some members of the phylum Campylobacterota (formerly Epsilonproteobacteria), including Helicobacter pylori and Campylobacter jejuni, have been classified by WHO as “high priority pathogens” for research and development of new antimicrobials due to the rapid emergence and dissemination of resistance mechanisms against first-line antibiotics and the alarming increase of multidrug-resistant strains worldwide. Notably, these clinically relevant pathogens express a variety of TCRS and orphan response regulators, sometimes unique among its phylum, that control transcription, translation, energy metabolism and redox homeostasis, as well as the expression of relevant enzymes and virulence factors. In the present mini-review, we describe the signalling mechanisms and functional diversity of TCRS in H. pylori and C. jejuni, and provide an overview of the most recent findings in the use of these microbial molecules as potential novel therapeutic targets for the development of new antibiotics.